2006
DOI: 10.1111/j.0014-3820.2006.tb01890.x
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Selection, Random Genetic Drift, and Genetic Variation at the Major Histocompatibility Complex in Two Wild Populations of Guppies (Poecilia Reticulata)

Abstract: Abstract. Our understanding of the evolution of genes of the major histocompatibility complex (MHC) is rapidly increasing, but there are still enigmatic questions remaining, particularly regarding the maintenance of high levels of MHC polymorphisms in small, isolated populations. Here, we analyze the genetic variation at eight microsatellite loci and sequence variation at exon 2 of the MHC class IIB (DAB) genes in two wild populations of the Trinidadian guppy, Poecilia reticulata. We compare the genetic variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 83 publications
3
75
3
Order By: Relevance
“…First, in our data the number of Gyrodactylus parasites infecting each fish did not explain significant variation in guppy condition (see the electronic supplementary material, S1.4), and second, despite several previous studies, evidence has not yet been found for a consistent difference in resistance or infection load between predation regimes (e.g. [10][11][12]). …”
Section: Discussioncontrasting
confidence: 72%
“…First, in our data the number of Gyrodactylus parasites infecting each fish did not explain significant variation in guppy condition (see the electronic supplementary material, S1.4), and second, despite several previous studies, evidence has not yet been found for a consistent difference in resistance or infection load between predation regimes (e.g. [10][11][12]). …”
Section: Discussioncontrasting
confidence: 72%
“…Briefly, an average of 14 fish from each population (range: 11-17) were genotyped at the MHC class IIB gene using a combination of single strand conformation polymorphism (SSCP), cloning and sequencing (see Fraser et al 2009 for full details). The MHC class IIB reading frame was determined by aligning our sequences with the reading frame identified for the guppy in van Oosterhout et al (2006) and three species of African cichlids (Haplochromis lividus, Oreochromis alcalicus, and Aulonocara hansbaenschi) (Figueroa et al 2000;Ono et al 1993). The amplified 230 bp were subsequently trimmed to 218 bp and 72 codons that constituted an open reading frame.…”
Section: Methodsmentioning
confidence: 99%
“…The amplified 230 bp were subsequently trimmed to 218 bp and 72 codons that constituted an open reading frame. The MHC class IIB gene is duplicated in the guppy and therefore individuals can have up to four different alleles (McConnell et al 1998;van Oosterhout et al 2006). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations